Interplay of adiponectin and resistin in type 2 diabetes: Implications for insulin resistance and atherosclerosis - Rawan Abudalo; Abdelrahim Alqudah; Esam Qnais; Rabaa Y. Athamneh; Muna Oqal; Roaa Alnajjar (Pensoft Publishers, 2024)
Aim: The study aims to investigate the association between type 2 diabetes and adipokines, particularly resistin and adiponectin, in insulin resistance. It also explores the potential of the resistin to adiponectin ratio as an indicator for these conditions Methods: This research involved 198 participants, including 100 patients with type 2 diabetes and 98 controls. It focused on measuring various biochemical parameters like HbA1c, fasting plasma glucose, lipid profiles (low-density lipoprotein, oxidized low-density lipoprotein, triglyceride, total cholesterol), and adipokines (resistin and adiponectin). The study utilized the Homeostasis Model Assessment of Insulin Resistance and Triglyceride-Glucose index to evaluate insulin resistance. Results: Type 2 diabetic patients exhibited higher levels of HbA1c, fasting plasma glucose, lipid profiles, and resistin, but lower adiponectin levels compared to controls. Adiponectin showed a negative correlation with insulin resistance, while resistin demonstrated a positive correlation. Both adipokines significantly related to atherogenic markers, with adiponectin offering protection against atherosclerosis and resistin augmenting it. Conclusion: The findings underscore the complex roles of resistin and adiponectin in the pathophysiology of type 2 diabetes, insulin resistance. The resistin to adiponectin ratio could be a useful biomarker for insulin resistance. These insights suggest potential therapeutic strategies for treating diabetes and preventing its complications.